Experimental and Numerical Analyses of the Thermal Regime of a Traditional Embankment in Permafrost Regions - Qihang Mei; Ji Chen; Shouhong Zhang; Xin Hou; Jingyi Zhao; Jinchang Wang; Haiming Dang; Guojun Liu; Guilong Wu (Advances in Materials Science and Engineering)
Traditional embankment is widely used in the permafrost regions along the Qinghai-Tibet Railway (QTR) because of its simple construction and lower cost. However, this form of embankment has insufficient ability to resist external thermal disturbance. To clarify the thermal characteristics of traditional embankment under climate warming, the ground temperature change process of section K1068 + 750 of the QTR was analysed in this study. Based on the field monitoring data from 2006 to 2019 and the established heat transfer model, the past and future changes of permafrost thermal regime under the embankment were analysed. The results show that the degradation of permafrost under the embankment is faster than that under the undisturbed site due to the combined of embankment construction and climate warming. The sunny-shady slope effect related to embankment orientation makes the distribution of permafrost temperature under embankment asymmetric. In the long term, permafrost degrades both under the undisturbed site and embankment. The continuous degradation of permafrost causes the settlement and deformation of embankment, especially the asymmetric degradation of permafrost on sunny side and shady side will cause longitudinal cracks on the embankment. Therefore, timely application of strengthening measures which can slow down the degradation of permafrost and adjust the uneven ground temperature on the sunny and shady sides under the embankment is of great significance to the safety of the traditional embankment.